Comparative Study of Self-Concept, Reference Group, Marketing Strategy, and Online Buying Behavior Accros Generation - Banafie, Syahfira; Simanjuntak, Megawati (Universitas Mercu Buana, 2023)
The development of an increasingly rapid era. One of them is the internet, which affects the necessities of life, and many bring changes in consumer lifestyles, namely alternative online buying methods. Online shopping increases market growth by providing goods that attract consumers' attention. Purchasing behavior for the sake of necessities of life can be driven by differences in the age of each generation, personal characteristics, environmental factors, and marketing promotions. This study aims to compare and analyze the influence of self-concepts, reference groups, and marketing strategies on online buying behavior in the Baby Boomer generation, generation X, and generation Y. The research data used descriptive analysis, different tests using the SPSS 22.0 application, and the influence test with the SEM method through the Smart Partial Least Square (PLS) program. The analysis of self-concept significantly affects online purchasing behavior in all generations, the Baby Boomer generation and all generations.